Laminin-111 Improves the Anabolic Response to Mechanical Load in Aged Skeletal Muscle. (7th December 2020) - Garg, Koyal; Mahmassani, Ziad S; Dvoretskiy, Svyatoslav; Valero, M Carmen; Huntsman, Heather D; Lapp, Samuel; Wu, Yu-Fu; Hauschka, Stephen D; Burkin, Dean J; Boppart, Marni D
Abstract: Anabolic resistance to a mechanical stimulus may contribute to the loss of skeletal muscle mass observed with age. In this study, young and aged mice were injected with saline or human LM-111 (1 mg/kg). One week later, the myotendinous junction of the gastrocnemius muscle was removed via myotenectomy (MTE), thus placing a chronic mechanical stimulus on the remaining plantaris muscle for 2 weeks. LM-111 increased α7B integrin protein expression and clustering of the α7B integrin near DAPI + nuclei in aged muscle in response to MTE. LM-111 reduced CD11b + immune cells, enhanced repair, and improved the growth response to loading in aged plantaris muscle. These results suggest that LM-111 may represent a novel therapeutic approach to prevent and/or treat sarcopenia.